2019
DOI: 10.1111/jbg.12445
|View full text |Cite
|
Sign up to set email alerts
|

Multiple domestication of swamp buffalo in China and South East Asia

Abstract: The domestication of swamp buffalo (Bubalus bubalis carabanesis) has been discussed for years and still remained unclear. To obtain a better understanding of where, when and how the swamp buffaloes were domesticated, the complete mitochondrial DNA D-loop sequences of 1,788 individuals from China, Vietnam, Laos,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
5
13
0
Order By: Relevance
“…Here, we found that the SB3 haplogroup was also detected in the Fuzhong buffalo, though with only two individuals. Our results showed that the haplogroup SA1 dominated in Fuzhong (45%) and Xilin buffalo (55%), and thus were consistent with previous studies based on the mtDNA control region and cytochrome b gene [4,6]. Furthermore, the haplogroup SA1 showed a star-like phylogeny, which was in accordance with the results of previous studies [4,6,8,17].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Here, we found that the SB3 haplogroup was also detected in the Fuzhong buffalo, though with only two individuals. Our results showed that the haplogroup SA1 dominated in Fuzhong (45%) and Xilin buffalo (55%), and thus were consistent with previous studies based on the mtDNA control region and cytochrome b gene [4,6]. Furthermore, the haplogroup SA1 showed a star-like phylogeny, which was in accordance with the results of previous studies [4,6,8,17].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we detected five haplogroups (SA1, SA2, SB1, SB2, SB3) in the Guangxi buffalo. Previous studies have detected four haplogroups (SA1, SA2, SB1, SB2) in the Fuzhong buffalo, while five haplogroups (SA1, SA2, SB1, SB2, SB3) were observed in the Xilin buffalo [4,6]. Here, we found that the SB3 haplogroup was also detected in the Fuzhong buffalo, though with only two individuals.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations